2013
DOI: 10.1007/s10482-013-9890-8
|View full text |Cite
|
Sign up to set email alerts
|

A new nematicidal compound produced by Streptomyces albogriseolus HA10002

Abstract: Strain HA10002 was isolated from mangrove sediment collected from Dongzhaigang Mangrove Reserve in Hainan, China. It was selected with potent nematicidal activity and was identified as Streptomyces albogriseolus. By bioassay-guided fractionation, a new active component A22-1(S1) against root-knot nematodes was separated from its fermentation broth. On the basis of spectroscopic analyses and comparison with the data from correlative literature, the structure of S1 was established to be 6′-methyl-fungichromin, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…4 ). All of these taxa are members of the Actinobacteria, which include many populations that have been shown to promote plant growth, mobilise nutrients and suppress bacterial, fungal or viral phytopathogens 26 27 28 29 30 . For this reason, the observed changes in the relative abundances of actinobacterial populations in our study, may have had functional consequences for the host, which deserve further investigation in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). All of these taxa are members of the Actinobacteria, which include many populations that have been shown to promote plant growth, mobilise nutrients and suppress bacterial, fungal or viral phytopathogens 26 27 28 29 30 . For this reason, the observed changes in the relative abundances of actinobacterial populations in our study, may have had functional consequences for the host, which deserve further investigation in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…So far, many nematicidal agents have been discovered from microorganisms such as bacteria, and fungi , which suggested that the microorganism‐based resources could serve as an abundant reservoir to explore the effective nematicidal agents. In this work, several compounds were obtained from SMrs28.…”
Section: Resultsmentioning
confidence: 99%
“…on plant parasitic nematodes. Recently a new nematicidal compound named as fungichromin B produced by Streptomyces albogriseolus was isolated against M. incognita which is having antifungal properties also (Qingfei Zeng et al, 2013). Similarly Nematicidal activity of fervenulin isolated from a nemati- cidal actinomycete, Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%